STATUS PEMANFAATAN BERDASARKAN UKURAN IKAN HIAS INJEL NAPOLEON POMACANTHUS XANTHOMETAPON DI PERAIRAN SULAWESI SELATAN - Mauli Kasmi (JURNAL GALUNG TROPIKA, 2013)
This research aims at: 1) Determine the utilization of fish in the waters injel napolen South Sulawesi. 2) Knowing the production rate under on sustainability stocks in the waters of South Sulawesi. 3) to analyze the size and age structure of fish in the waters injel napolen South Sulawesi. The basic method used in this research is descriptive and explanatory. Kinds of data in this study based dimensiwaktu, the time series data (time series) and cross section (cross-points) and the weight of the fish length.The Status of analysis is the use of the model to determine the relationship FOX CPUE and effort. The composition of the length and weight of fish length injel napoleon analyzed descriptively in tables and graphs with units or percentages.Injel napoleon fish caught is where 53% of young fish gonadnya undeveloped, 26% female, 14% male and 7% hermaphrodites. While fekunditasnya not be determined because gonadnya undeveloped. Size of the fish were caught ranging in size from 4.3 cm which is dominated by the size of 8.1 to 11 cm (38.4%) and the size from 11.1 to 15 (29.4%). While the size of the largest was 15.1 - 25 cm which is only 6.7%. Length relationships are allometrik weight, growth rate of 0.4934 cm / yr with a maximum length of 41.7 cm at the age of 13 years. Examples of fish obtained 1.5 years old, age of first arrest 151 days and the age of first spawning of 2.5 years.